Mazzuca, Sebastián: Latecomer State Formation. Political Geography and Capacity Failure in Latin America, New Haven & London, Yale University Press, 2021. 447 pp. - Cortesi, Sebastián G. (Cuadernos de Historia Contemporánea, 2021)
Reseña de la obra de Mazzuca, Sebastián: Latecomer State Formation. Political Geography and Capacity Failure in Latin America, New Haven & London, Yale University Press, 2021. 447 pp.